Handbook for Brunner & Suddarth's textbook of medical-surgical nursing. (Philadelphia, Pennsylvania : Wolters Kluwer, Lippincott Williams & Wilkins, 2010)
"This concise clinical companion to the twelfth edition of Brunner and Suddarth's Textbook of Medical-Surgical Nursing presents nearly 200 diseases and disorders in alphabetical format, allowing rapid access to need-to-know information on the most commonly clinical problems nurses are likely to encounter. The content is completely cross-referenced to the main text. Pages are tabbed alphabetically for speedy reference."--Publisher
Includes index.
Keywords: SURGICAL NURSING HANDBOOKS, MANUALS, ETC